Extracellular Biosynthesis of TiO2 Nanoparticles Using Supernatant Culture of Lactobacillus crispatus - Kawther H. Ibrahem (Journal of Global Pharma Technology, 2016)
In this study, titanium dioxide nanoparticles were synthesized biologically using isolated L.crispatus from vagina of healthy women. The formation of TiO2 nanoparticles was characterized by atomic force microscope (AFM) using supernatant culture of L.crispatus .Extracellular biosynthesized TiO2 nanoparticles occurred with the average size (87.88) nm. For further characterization, the x-ray diffraction (XRD), energy dispersive x –ray spectroscopy (EDX), and scanning electron microscope (SEM) were used. XRD Confirmed the formation of crystallographic plane of anatase of TiO2 nanoparticles indicating that nanoparticles corresponded to anatase crystalline, while the EDX analysis of TiO2 nanoparticles indicated that the synthesized nanoparticles were anatase form and not frutile or brookite form. The SEM images of the synthesized TiO2 nanoparticles were showed spherical or oval in shape. The effect of independent variables, including different incubation times and storage condition on the biosynthesis of TiO2 nanoparticles was investigated. The average size (70.98)nm of TiO2 nanoparticle was observed after 72 h .The stability of the synthesized TiO2 nanoparticles for (1,2,3)months under cooling condition was studied and the result revealed that the synthesized TiO2 nanoparticle remained stable without change in color even after storage for three months under cooling conditions.Keywords: TiO2 nanoparticles; Biosynthesis; Lactobacillus Crispatus; Incubation time; Storage time.